2012
DOI: 10.1089/tmj.2011.0089
|View full text |Cite
|
Sign up to set email alerts
|

Teleophthalmology Assessment of Diabetic Retinopathy Fundus Images: Smartphone Versus Standard Office Computer Workstation

Abstract: Ophthalmic images transmitted through both smartphone and Internet techniques match well with each other. Despite current limitations, smartphones could represent as a tool for fundus photo assessments of diabetic retinopathy. Further studies are needed to investigate the economic and clinical feasibility of smartphones in ophthalmology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 8 publications
0
43
0
2
Order By: Relevance
“…Similarly, Kumar et al 31 showed that retinal images of patients at minimum with moderate severity of diabetic retinopathy when read by a specialist on a smartphone achieved high concordance with images read on a standard office computer workstation. However, the study was limited by the small number of images with early, more subtle pathology being included for comparison.…”
Section: Ophthalmologymentioning
confidence: 94%
“…Similarly, Kumar et al 31 showed that retinal images of patients at minimum with moderate severity of diabetic retinopathy when read by a specialist on a smartphone achieved high concordance with images read on a standard office computer workstation. However, the study was limited by the small number of images with early, more subtle pathology being included for comparison.…”
Section: Ophthalmologymentioning
confidence: 94%
“…Reports show increased penetration of mobile devices compared to that of computers. [7] Improved communication capabilities (e.g. 3G) also happened during this time.…”
Section: M-healthmentioning
confidence: 97%
“…Touch enabled mobile devices make image review and template based reporting, very easy for the user.Specificity and Sensitivity of use of iPhone for TeleOphthalmology has been published. [7] 4 Decision Support Using Image Processing…”
Section: Fig 3 Physician Reporting Via Iphonementioning
confidence: 99%
“…Owing to their handy and connectable nature, these devices will be very valuable in remote diagnosis. Kumar et al [11] used an iPhone-based specific image archiving and forwarding program (i2i telesolutions) to view and report the diagnosis on diabetic retinopathy fundus images in the mobile phones. It was found that the diagnosis using mobile phones matched with that of computer-based technique, and the quality of images on the iPhones was reported high by the ophthalmologists.…”
Section: Mhealth In Diagnosismentioning
confidence: 99%